The Moral Values of Syi’ir Ngudi Susilo in Building of Children’s Character - Moh Hasim (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This research was motivated by a condition that reading of Syi’ir as a culture in societydecreased. Whereas, Syi’ir contained a lot of good values related to children’s character building. Through field research method, philology, and documentary research, this study found that Syi’ir Ngudi Susilo was Syi’ir that contains children’s moral value to build their character. Syi’ir Ngudi Susilo consists of a very useful basic moral value to develop of children’s character. The Basic moral embedded in Syi’ir Ngudi Susilo were respect and responsibility. Respect would bring children to have polite in personality and behavior based on the moral value. From respect, children would have a responsible character that would create self-consciousness to do moral act. By those two basic moral values, respect and responsibility, then children would grow with noble characters.